1990
DOI: 10.1111/j.1475-2743.1990.tb00823.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of land management on concentrations of dissolved organic carbon and its effects on the mobilization of aluminium and iron in podzol soils in Mid‐Wales

Abstract: Abstract. The aluminium (Al), iron (Fe) and Dissolved Organic Carbon (DOC) contents of the soil solution were monitored in two upland grassland and afforested podzol soils in Mid‐Wales. Al organo‐metallic complexes predominated in the O horizon leachates of the grassland soil, whereas inorganic monomeric Al forms dominated in the lower mineral horizons. Dissolved organic matter determines the chemistry, solubility, and transport of Al and Fe in the O horizon, and these are under strong biological control. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…Over the longer term, increases in DOC concentrations at felled sites are generally indistinguishable from trends observed more widely in UK rivers (Neal et al, 2005). The stream water response is not consistent with the large short-term increases in the concentrations of DOC observed in surface organic horizon soil waters at felled sites on organo-mineral soils (Hughes et al, 1990). The soil water response can be attributed to site disturbance, an increase in summer soil temperatures due to a change in microclimate following removal of shade and an increase in nutrient supply from the felling debris stimulating microbial activity in the organic surface horizons (Zech et al, 1994).…”
Section: Forest Harvestingcontrasting
confidence: 56%
See 1 more Smart Citation
“…Over the longer term, increases in DOC concentrations at felled sites are generally indistinguishable from trends observed more widely in UK rivers (Neal et al, 2005). The stream water response is not consistent with the large short-term increases in the concentrations of DOC observed in surface organic horizon soil waters at felled sites on organo-mineral soils (Hughes et al, 1990). The soil water response can be attributed to site disturbance, an increase in summer soil temperatures due to a change in microclimate following removal of shade and an increase in nutrient supply from the felling debris stimulating microbial activity in the organic surface horizons (Zech et al, 1994).…”
Section: Forest Harvestingcontrasting
confidence: 56%
“…It seems that the DOC in soil waters is not reaching surface or groundwaters, suggesting that it may be mineralised en route or immobilised in the mineral soil horizons (Table 11; Hughes et al, 1990 andZech et al, 1994). In the latter case, the carbon would be largely retained on site although the efficiency of this process may be impeded by saturation of sorption sites by the increased DOC flux.…”
Section: Forest Harvestingmentioning
confidence: 99%
“…Iron follows a similar trend because it is strongly chelated to dissolved organic matter. The coupling of DOC and Fe has been observed previously in soil waters and stream waters in upland catchments in mid-Wales (Hughes et al, 1990(Hughes et al, , 1998Neal et al, 2001). Be concentrations also increase over time but the Be data cover only the first two thirds of the data record: the trend for Be is observed at a different site in mid-Wales (Neal, 2003).…”
Section: Temporal Patterns For the Streamsmentioning
confidence: 81%
“…Microorganisms prefer to consume non-humic substances like sugars as opposed to humic acids which are not as easily broken down (Clark et al 2010). Hughes et al (1990) reported that higher weight DOC molecules are found in forest soils, whereas more labile forms of DOC are found in agricultural soils (Delprat et al 1997). As the amount of agricultural land in a watershed increases, the proportion of recalcitrant DOC in the outlet stream diminishes (Cronan et al 1999).…”
Section: Dissolved Organic Carbonmentioning
confidence: 99%
“…In the short-term following a forest clearcut and subsequent tillage to prepare the soil for agriculture, several studies reported an initial increase in DOC concentrations from 10 to 150 mg L -1 due to mobilization of SOC in the form of DOC (Hughes et al 1990, Qualls et al 2000. Total DOC export from agricultural watersheds decreased over the long-term, however, because of lower organic matter input to the soil and stabilization of the remaining organic matter.…”
Section: Dissolved Organic Carbon and Watershed Land Usementioning
confidence: 99%